2016
DOI: 10.1177/0022002715595701
|View full text |Cite
|
Sign up to set email alerts
|

Donor Fragmentation, Aid Shocks, and Violent Political Conflict

Abstract: Recent debates have focused on the negative role of the proliferation of foreign aid facilities and donor fragmentation for development outcomes and recipient country institutions. This article investigates an overlooked positive side effect of donor proliferation. With an increasing number of donors, exposure to negative aid shocks decreases, as well as the impact of such shocks on violent political conflict. Using data on 106 recipient countries for the years 1970 to 2008 and employing event history and medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…The observed bypassing of the Ministry of Health through the use of NGOs reflects donors' practice in fragile states (Acht, Mahmoud, and Thiele 2014;Dietrich 2013;Gutting and Steinwand 2017). Although there are some positive aspects of collaborating with NGOs, there are challenges (Banks and Hulme 2012;Banks, Hulme, and Edwards 2015;Buse and Walt 1996;Doyle and Patel 2008;Gideon and Porter 2016;Hearn 1998Hearn , 2007Pfeiffer 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The observed bypassing of the Ministry of Health through the use of NGOs reflects donors' practice in fragile states (Acht, Mahmoud, and Thiele 2014;Dietrich 2013;Gutting and Steinwand 2017). Although there are some positive aspects of collaborating with NGOs, there are challenges (Banks and Hulme 2012;Banks, Hulme, and Edwards 2015;Buse and Walt 1996;Doyle and Patel 2008;Gideon and Porter 2016;Hearn 1998Hearn , 2007Pfeiffer 2003).…”
Section: Discussionmentioning
confidence: 99%
“…One out of the three studies found a direct effect on civil conflict onset [46,82,83], and the three studies that analyze incidence, duration, and battles also find these to be more likely in the wake of a disaster [46,57,84] (not in Table 1). Overall, in the period under review, too few studies were conducted to draw firm conclusions, but as for temperature, results opposite of the scarcity scenario seem unlikely.…”
Section: Empirical Studies 2014-2017mentioning
confidence: 99%
“…A poor environment may lead to increased levels and as the environment improves membership levels decrease. Gutting and Steinwand () focused on the relationship between donor fragmentation, aid shocks, and political instability. Rejecting the belief that donor concentration can lead to disruptions in economic and political systems, the authors suggest that fragmentation reduces the impact of aid shocks and hence political instability as well (p. 663).…”
Section: Political Stability In Country Of Operationmentioning
confidence: 99%